Grit: a strenght that needs balance - the risk of crossing the ethical red line - Santos, Catarina Capelo Ramos Nunes dos (2017)
"Grit” is an evolving concept that has been perceived in different ways, by different people, in different times. The question that should be answered with this WP, to address the risk that grit without ethics can present, is: “Where does the red line stand between grit being a strength or becoming an issue?”. The analysis of the answers to quantitative and qualitative surveys that were conducted will enable to better understand if, when and why people can lose their ethics along their academic or professional journey and grit can become a problem rather than a praised positive character trait.